Perceptions of Borders and Human Migration : The Human (In)Security of Shan Migrant Workers in Thailand - Ropharat Aphijanyatham (Institut de recherche sur l'Asie du Sud-Est contemporaine, 2009)
While there are many prior studies to date on the internal conflicts in Burma, these are mostly focused on the human rights situation within the country. In addition, many previous marked studies, such as works from Thai academics, International Organizations or the World Health Organization, have highlighted the human securities of migrant workers in the destination country whereby the process of migration has already taken place. However, none of them have focused on the phenomenon of migration in relation to perceptions of borders and human security. The lack of study addressing the influence of borders and human securities as the key indicators to people's migration behaviour supports the significance and relevance of this research.